Are Minimum Wages a Silent Killer? New Evidence on Drunk Driving Fatalities - Sabia, Joseph J.; Pitts, M. Melinda; Argys, Laura M. (The Review of Economics and Statistics, 2019)
Abstract In volume 94 of this REVIEW, Adams, Blackburn, and Cotti (ABC), using Fatal Accident Reporting System data from 1998 to 2006, find that a 10% increase in the minimum wage is associated with a 7% to 11% increase in alcohol-related fatal traffic accidents involving teen drivers. We find this result does not hold when the analysis period is expanded to include 1991 through 2013. In addition, auxiliary analyses provide no support for income-driven increases in alcohol consumption, the primary mechanism posited by ABC. Together, our results suggest that minimum wage increases are not a silent killer.